Heavy metals in atmospheric deposition in Málaga (SE Spain) and the influence of African dust intrusions - Liger-Pérez, Esperanza; Cañada, Pedro; González, Rocío; Tuite, Patrick; Ramírez, Teodoro; Gordo Puertas, Elisa; Cabello Ganuza, María; Cañete-Hidalgo, Sergio Andrés; Dueñas-Buey, Mª Concepción (My University, 2018)
This study reports information on deposition samples collected weekly at a coastal sampling site (Málaga, SE Spain) as part of a research project focused on the impact of atmospheric deposition on the Alborán Sea (W-Mediterranean). This semi-enclosed basin is a transitional area between the Atlantic Ocean and the Mediterranean. Moreover, due to its geographical location the area is frequently affected by intrusions of air masses loaded with high concentrations of atmospheric particulate matter. Major and trace metal analysis of filters and filtrates were aiming at finding the dissolved and non-dissolved fractions of the deposited material. The origin of the air masses reaching the study region was interpreted based on back-trajectories and principal component analysis was performed to find out the groups of elements with similar behaviour. Deposition fluxes at this site were marked by meteorological conditions and the external influence of other sources on a regional scale and the frequency and magnitude of African dust intrusions.
Keywords: Deposición atmosférica; Atmospheric deposition; metals; African dust intrusions; Mediterranean Sea